Legal measures to access and utilize State Information and Protecting Information Providers - สุนทรอนันตชัย, ธนาชัย; ปาลวงษ์พานิช, ปกรณ์; สุขนิวัฒน์ชัย, กษมา (Huachiew Chalermprakiet Law Journal, 2018)
The objectives of this research are to reexamine and analyze the law regarding access and utilization of state information and also the law as to informant protection. Moreover, this paper will suggest guidelines and legal measures to access and utilize of state information and informant protection. The qualitative research methods are documentary research and interviews. The results have been found that Thai citizens are able to access and utilize of state information under affirmation and protection of “Right to Information” Meanwhile, an informant providing information to state or private section has received “Right to Privacy” protection.These rights mentioned above have been affirmed and protected by the international community and national law of various jurisdictions including Thailand. These rights are significant to promote public participation in politics, sustainable development and adaptation of public and private sectors to the Digital Age. However, the researcher discovered that there are several crucial obstacles with respect to law enforcement to protect such rights such as the problem of state officer discretion, conflict of laws, right security of decisions of Information Disclosure Tribunals, ineffective law enforcement, right to privacy violation and so on. Suggestions are stated in this paper which are the revision of Official Information Act, B.E. 2540 especially the definition of “Public Information,” Information types stipulation that has to be widely disseminated and private information protection standard is supposed to be revised and the meaning of “Personal Information in State Agency” shall be defined. Furthermore, the state information should be reformed to be able to utilize, the discretion in making decisions of state officers is supposed to be appropriate and the Private Information Protection enactment, B.E. … shall be accelerated and specified the scope of this act, work mechanism, sanctions and consideration of work mechanism connection between entities subjected to this act and other organizations according to the Official Information Act, B.E. 2540 to be apparent, correspondent and appropriate.